PRECURSORS OF THE DEVELOPMENT OF TROPHOBLASTIC DISEASE AMONG WOMEN OF REPRODUCTIVE AGE (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
According to literature data, trophoblastic disease is characteristic only of pregnant women of reproductive age and occurs in 0.1-0.25% of all pregnancies. Cystic fibrosis is most often diagnosed among this pathology.